(untitled) (Revista Sistemas de Producción Agroecológicos, 2011)
Livestock production systems have changed as the world population grows, this growth as high social has led to intensive farms need more animals for better production technologies. The growth of productive systems favored the emergence of infectious and parasitic diseases that require the use of drugs with therapeutic or prophylactic purposes, in addition the use of these products are being used fraudulently as growth promoters, are also used as stress reducers during transport to improving the quality of the product. The use of drugs in animal production is not controlled or supervised by the relevant entities which results in inappropriate medication use on farms. Worldwide production of drugs for animal brings more than 14.9 billion dollars of which 59.8% correspond to products intended for production systems, of which the parasite represent 28.4%, biological (vaccines) 22.6%, antibiotics15.8%, additives13% and other medicated 20.2%.